Toward person-centred measures of contraceptive demand: a systematic review of the relationship between intentions to use and actual use of contraception. [version 3; peer review: 1 approved, 2 approved with reservations] - Christine Galavotti; Kelsey Quinn Wright; Victoria Boydell; Shatha Elnakib (Gates Open Research)
Background Understanding people’s interest in using modern contraception is critical to ensuring programs align with people’s preferences and needs. Current measures of demand for contraception are misinterpreted. More direct measures of intention to use (ITU) contraception do exist but remain underexplored. This systematic review examines the relationship between intention to use and actual use of contraception. Methods We searched PubMed, PsycInfo, Web of Science, and the Cochrane Collaboration to identify studies published from 1975-2020 that: (1) examined contraceptive behaviour, (2) included measures of ITU and future contraceptive use, and (3) included at least one quantitative measure of association between ITU and actual use. The inclusion criteria were: 1) examined contraceptive behaviour (excluding condom use only), (2) included disaggregated integral measures of ITU contraceptives and later contraceptive use, (3) included at least one quantitative measure of the association between ITU contraceptives and actual contraceptive use, (4) study population was women of reproductive age, (5) were peer-reviewed, and (6) written in English. Results 10 prospective cohort studies met the inclusion criteria; these provided 28,749 person-years of data (N=10,925). Although we could pool the data for unadjusted odds ratios, a metanalysis was not possible. We calculated that 6 of the 10 studies indicated significant, increased, unadjusted odds of subsequent contraceptive use after reporting ITU. Of those, 3 study analyses reported significant, positive adjusted odds ratios for the relationship between intention to use and later contraceptive use across varying covariates. The range of confounding factors, particularly around sub-populations, points to the need for more research so that a meta-analysis can be done in the future. Conclusions People’s self-reported ITU contraception has the potential to be a strong predictor of subsequent contraceptive use. Few studies directly examined the relationship between ITU and contraceptive uptake and recruitment was primarily pregnant or postpartum samples.